2014
DOI: 10.1603/en13023
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Enrichment Affects Immature Mosquito Abundance and Species Composition in Field-Based Mesocosms in the Coastal Plain of Georgia

Abstract: This study is the first to examine the relationship between nutrient enrichment and oviposition preference as measured by larval mosquito abundance using field-based mesocosms adjacent to wetlands in the Gulf Coastal Plain of Georgia. Agricultural wetlands in this region are known to have higher levels of nutrients and suspended sediments compared with forested wetlands, and previous studies have shown differences in mosquito communities in agricultural and forested wetlands. The purpose of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
6
0
3
Order By: Relevance
“…albopictus larval densities increased with nitrite and nitrate concentration, and declined with dissolved solids, and Young et al . () found that Ae. albopictus larval numbers were greater in fertilized field mesocosms that had higher phosphate levels than in unfertilized field mesocosms; these findings suggest that both the P and N components of NPK fertilizer may be attractive to gravid female Ae.…”
Section: Discussionmentioning
confidence: 98%
“…albopictus larval densities increased with nitrite and nitrate concentration, and declined with dissolved solids, and Young et al . () found that Ae. albopictus larval numbers were greater in fertilized field mesocosms that had higher phosphate levels than in unfertilized field mesocosms; these findings suggest that both the P and N components of NPK fertilizer may be attractive to gravid female Ae.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in the Gulf Coastal Plain have shown differences in mosquito community composition between agricultural and forested wetlands (Botello et al ), and nutrient‐enriched containers showed greater oviposition preference by larval mosquitoes (Young et al ). Therefore, we were interested in determining which food resources are available and assimilated by larval mosquitoes in agricultural wetlands.…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, nutrient subsidies leading to increased food resources (e.g. phytoplankton) in aquatic systems can enhance the recruitment of Culex restuans (Reiskind and Wilson 2004, Young et al 2014. If both increased salinity and nutrient enrichment increase mosquito recruitment through survival and emergence, then we would expect that road salts combined with organic additives would increase recruitment more than salt alone.…”
Section: Introductionmentioning
confidence: 99%